(3cJGH aj GdgfOSjGJs - (3CHhSgd Gdbhgjs
(3ChdgG (B:s
(3HYO GdHSedI Gbhd HYO MeO Gddg hNUhUkG GdgfOSjGJ aj hVhM eSGcdgG hbhGYOgG s
(3BNQgG (B:s
(3hPdc eG GQOfG Gf fHjf hfJe gPg GdCTcGd s
(3Vef eLehY , JQJjHgG (B: 1s
(3HgG fXGe GdJYbjHIs
(3hjJdhgG fbd aj GdgfOSIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3GjGUhajG (B(1760) s
Keywords: (3eJaQbGJs